L’image de la guerre dans L’Élan (1915-1916), un refoulement apparent - Hadrien Viraben (Les Cahiers de l'École du Louvre)
In 1915 Amédée Ozenfant founded the magazine L’Élan. For two years, it published in Paris the works of well and lesser-known artists who featured in the pre-war cubist magazines, including Derain, Dunoyer de Segonzac, Favory, Fauconnet, Laboureur, La Fresnaye, Lespinasse, Lhote, Marchand, Metzinger, Moreau, Picasso and Severini. The magazine still has a reputation for having had turned a blind eye to contemporary events, and for having censored gory war pictures. The present article aims to reconsider this idea by demonstrating that the violence of the time had, on the contrary, profoundly affected the works of these artists. This violence, located between representation and a latent image, could thus materialise at any moment in the pages of the magazine.